Ternary organic photodetectors based on pseudo–binaries nonfullerene–based acceptors - Zhang,T; Moser,M; Scaccabarozzi,A; Bristow,H; Jacoutot,P; Wadsworth,A; Anthopoulos,T; McCulloch,I; Gasparini,N (Journal of Physics: Materials, 2021)
The addition of a third component to a donor:acceptor blend is a powerful tool to enhance the power conversion efficiency of organic solar cells. Featuring a similar operating mechanism, organic photodetectors are also expected to benefit from this approach. Here, we fabricated ternary organic photodetectors, based on a polymer donor and two nonfullerene acceptors, resulting in a low dark current of 0.42 nA cm−2 at −2 V and a broadband specific detectivity of 1012 Jones. We found that exciton recombination in the binary blend is reduced in ternary devices due to the formation of a pseudo-binary microstructure with mixed donor–acceptor phases. With this approach a wide range of intermediate open-circuit voltages is accessible, without sacrificing light-to-current conversion. This results in ternary organic photodetector (TOPD) with improved Responsivity values in the near-infrared. Moreover, morphology analyses reveal that TOPD devices showed improved microstructure ordering and consequentially higher charge carrier mobilities compared to the reference devices.